Subtherapeutic Anticoagulation Control under Treatment with Vitamin K-Antagonists—Data from a Specialized Coagulation Service - Prochaska, Jürgen H.; Hausner, Christoph; Nagler, Markus; Göbel, Sebastian; Eggebrecht, Lisa; Panova-Noeva, Marina; Arnold, Natalie; Lauterbach, Michael; Bickel, Christoph; Michal, Matthias; Hardt, Roland; Espinola-Klein, Christine; Lackner, Karl J.; Münzel, Thomas; Wild, Philipp S. (Thrombosis and Haemostasis, 2019)
In contrast to overanticoagulation, evidence on risk factors and outcome of subtherapeutic oral anticoagulation (OAC) with vitamin K-antagonists (VKAs) under optimum care is limited. We investigated the clinical phenotype, anticoagulation control, and clinical outcome of 760 VKA patients who received OAC therapy by a specialized coagulation service in the thrombEVAL study (NCT01809015). During 281,934 treatment days, 278 patients experience ≥ 1 episode of subtherapeutic anticoagulation control and had lower quality of OAC therapy compared to 482 patients without subtherapeutic international normalized ratio: 67.6%, interquartile range (IQR) 54.9%/76.8% versus 81.0%, IQR 68.5%/90.4%; p < 0.001. In Cox regression analysis with adjustment for age, sex, cardiovascular risk factors, comorbidities, and treatment characteristics, female sex (hazard ratio [HR], 1.4, 95% confidence interval [CI], 1.0/1.9; p = 0.03), diabetes (HR, 1.4, 95% CI, 1.0/2.0; p = 0.03), and living alone (HR, 1.5, 95% CI, 1.1/2.1; p = 0.009) were independent risk factors of subtherapeutic anticoagulation control, whereas atrial fibrillation (HR, 0.6, 95% CI, 0.4/0.9; p = 0.02) and self-management of OAC therapy (HR, 0.2, 95% CI, 0.1/0.6; p = 0.001) were protective. In addition, active smoking (HR, 1.7, 95% CI, 0.9/3.0; p = 0.086) and living in a nursing home (HR, 1.6, 95% CI, 0.8/3.2; p = 0.15) indicated an elevated risk at the borderline of statistical significance. For the prediction of recurrent subtherapeutic anticoagulation, living alone was the only independent risk factor (HR, 1.7, 95% CI, 1.1/2.5; p = 0.013). The present study suggests that women, diabetics, and patients living alone experience an increased risk of low-quality VKA therapy and might potentially benefit from treatment with direct-acting anticoagulants.
Keywords: oral anticoagulation; vitamin K-antagonists; subtherapeutic INR; risk factors